Gender-Specific Inverse Associations Between Beans Intake, Serum Urate Levels, and Hyperuricemia: A Cross-Sectional Analysis Based on the Henan Rural Cohort Study - Cui, Ningning; Dong, Xiaokang; Xue, Yuan; Liao, Wei; Liu, Xiaotian; Li, Yuqian; Hou, Jian; Huo, Wenqian; Li, Linlin; Mao, Zhenxing; Zheng, Zhaohui; Wang, Chongjian (Frontiers in Nutrition, 2021)
Abstract Background and Aims: Beans are rich in purines, which are important substances that lead to elevated serum urate, especially exogenous purines. Few studies were conducted to assess the relationship between beans intake and serum urate or hyperuricemia, especially in rural people. The purpose of this study was to validate the association by gender in the rural Chinese population. Methods: A total of 38 855 participants aged 18-79 years old were enrolled from the Henan Rural Cohort Study (Registration number: ChiCTR-OOC-15006699). Dietary data was collected using a validated food frequency questionnaire (FFQ). Linear regression models and logistic regression models were used to examine the associations between beans intake and serum urate levels or hyperuricemia. Restricted cubic spline regression was performed to display the dose-response relationship. Results: In multivariate-adjusted linear regression, an inverse correlation was found between beans intake and serum urate level (the highest quartile Q4 vs the bottom quartile Q1) in both men (P = 0.008) and women (P < 0.001). Per 10g increment in beans intake was associated with 0.30μmol/L decreased concentration of serum urate in men and 0.71μmol/L in women. The multivariate-adjusted odds ratios (ORs) of hyperuricemia were 0.83 (0.71, 0.97) in men and 0.73 (0.63, 0.84) in women (Q4 vs Q1). Per 10g increment in beans intake created a 1% decreased risk of hyperuricemia in men and 3% in women. The cubic spline suggested a risk reduction for hyperuricemia with increasing intake of beans. Conclusion: A higher beans intake was associated with a lower serum urate level and a reduced risk of hyperuricemia in both sexes, and the association was more pronounced in women.